The formulation of guidance objectives for secondary schools in Sri Lanka base on a survey of the guidance needs of children in selected schools in the Kandy region - Pararajasingam, G. (My University, 1978)
Guidance is the need of the hour in schools, for Sri Lanka today is perturbed by the unrest of its youth. The development of this branch of education which has frozen even prior to reaching infanthood in this Island, is the major responsibility of the “mentors of education destiny”. Highlighting the obstacles found in the development of student potential and thereby emphasising that the development of guidance would be a significant movement in education for it would easen the lives of tomorrow's generation s of students, are the centred aims of the writer. …